Efekty treningowe w przygotowaniu wysoko kwalifikowanych pilkarzy noznych: przeglad - Lyakh, V.; Bujas, P.; Gargula, L. (Journal of Kinesiology and Exercise Sciences, 2012)
Aim of the study. Team games including football are among the disciplines in which the assessment of individual training activities of athlete is difficult. This follows from incommensurability of effects - especially the sports competition. Thus becomes important to introduce more stable criteria and methods supporting a player and coach in the evaluation of the effectiveness of its preparation. Current science provides us many modern methods to monitor the post-training changes in athletes in the physiological-biochemical, mental as well as motor adjustments. The article is an analysis of modern approach to assess the course and the effectiveness of training impact on the example of football. Material and methods. Analysis of selected contemporary literature. Results. On the basis of various criteria and the size of functional indicators, authors present modern structure of training effects beyond the most commonly cited direct, prolonged and cumulative effects, by introducing the concept of remote and final training effects. Remote training effects are manifested in the delayed accumulation of influences of training on the change of competition outcome. They are particularly important in exteriorizing the coordination abilities and the maximum speed for which the level of fatigue-rest affects particularly the neuromuscular coordination. The final effects of training state the period during which an increased level of physical capability remains above reached immediately after cessation of the impact of specialist training. Because of time of the post-training changes in the body there are two sub-effects: short-and long-term ultimate effect. Much of the first one is particularly important for the control of training process. Conclusions. These training effects govern the interaction of coach and athlete. Understanding of their characteristics is essential for planning and analysis of the training process, making its effects more controllable and predictable.